A few remarks on "zero-Two" law for positive contractions in the Orlicz-Kantorovich spaces - Ganiev, Inomjon; Mukhamedov, Farrukh; Bekbaev, Dilmurad (IOP Publishing Ltd, 2017)
In this paper we establish a vector version the "zero-two" law for positive contractions in the Orlicz-Kantorovich spaces.